Gastrodiplomacy “Washoku” Jepang Di Amerika Serikat - Anggraeni, Dian; Kurniawati , Erna (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2018)
Since 2004, Japan used public diplomacy focusing in pop culture. Japan also conducted a kind of public diplomacy that using cuisine to promote the uniqueness of Japan culinary which known as gastrodiplomacy. Japan used washoku as an icon of its gastrodiplomacy. Washoku is chosen for its uniqueness, so it will increased the popularity of Japanese brand in the world. Japan selected United State to promote washoku for it is one of the washoku’s biggest market . This article is to provide the strategy, effort and effectiveness gastrodiplomacy washoku of Japan to United States that using many actors such as government, non state actors, businesses, private citizens, education sectors, and medias.